Vloga predmetnih didaktik za kompetence prihodnosti: zbornik povzetkov (University of Maribor Press, 2019)
The Role of Subject Didactics for the Competences of the Future: Book of Abstracts. The Faculty of Education of the University of Maribor is aware that education is one of the key development areas in every modern society. In addition, we face one of the biggest challenges of our time: how to train for the future. To this purpose, we organized an international scientific conference entitled The role of subject didactics for the competences of the future. With the conference, we would like to offer some answers and explore the processes, measures, challenges and results of learning and teaching. The conference book of abstracts presents findings from practitioners and researchers from a wide range of academic fields who are interested in researching and contributing to educational topics. Abstracts follow two main objectives of the conference: knowledge presentation of subject didactics in the field of competence development for the future and hearing and exchanging practical experiences, knowledge and good teaching practice between teachers and researchers. The book of abstracts covers several topics: developing student competencies (collaborative learning, cross-curricular learning and teaching, interdisciplinary teaching, differentiation and individualization, the principle of equality, consideration of preknowledge, learning by research, the role of mediators in teaching, authentic situations, modern e-learning environments (ICT), out-of-class learning, development of various types of literacies), triangle subject area, didactics and subject didactics (professional development of teachers, teachers’ self-reflection, contemporary approaches to teaching in practice, subject-pedagogical knowledge of teachers, the literacy abilities of students and teachers, reciprocity, proportionality and similarity of the subject area, didactics and subject didactics), visualization (visual literacy, encouraging specific perceptual abilities) and implementation of cognitive conflict in the classroom (cognitive humiliation of pupils, constructivism - cognitive conflict, misconceptions, intuitive concepts, cognitive schemes).